Software industry awareness on sustainable software engineering: a Brazilian perspective - Karita, Leila; Mourão, Brunna Caroline; Martins, Luana Almeida; Soares, Larissa Rocha; Machado, Ivan (Journal of software engineering research and development, 2021)
Sustainable computing is a rapidly growing research area spanning several areas of computer science. In the software engineering field, the topic has received increasing attention in recent years, with several studies addressing a range of concerns. However, few studies have demonstrated the awareness of software practitioners about the underlying concepts of sustainability in the software development practice. In this effect, this study aims to provide some evidence regarding the practitioners’ perception about the adoption of sustainability in software development, under four main perspectives: economic, social, environmental, and technical. In previous work, we carried out a preliminary survey study with twenty-five software engineers who work in a range of domains. The yielded results indicate an overall lack of knowledge about the topic, in particular, related to concepts about sustainable software. In this study, we extend the survey and reached a number of ninety-seven respondents. The novel results confirmed the evidence raised in the original survey that sustainability in the context of software is a new subject for software practitioners. However, professionals have shown interest in it. There is a general understanding that sustainability should be treated as a quality attribute. Among the observed perspectives, we generated an initial theory, which shows that software practitioners know the subject around ‘Green in Software’, even unconsciously. This study contributes to the green and sustainable software engineering field by bringing evidence on comprehending how the software industry understands the adoption of sustainability in the software development process.